The red sea falls upon Cimarron! - McWilliams, C.S. (Cimarron, NM Cimarron Legend, 1992)
Article on a massive storm that hit Cimarron and the surrounding area and the damage it caused.
Master List Item # 41
File location is in the New Mexico File Cabinets
Keywords: Kutz, Val; Coppage, Barney; Campanella, Eula; Cimarron Legend; Kit Carson; Cimarron Art Gallery; Summer rain; Flooding; Volunteer Firemen; Rescue; Damaged Crops; Cimarron, New Mexico; Sangre De Cristo; Maxwell, New Mexico